The Students' Creative Thinking Process based on Wallas Theory in Solving Mathematical Problems viewed from Adversity Quotient /Type Climbers - Yanti, Avissa Purnama; Koestoro, Budi; Sutiarso, Sugeng (Al-Jabar: Jurnal Pendidikan Matematika, 2018)
This research aims to describe the creative thinking process of students based on Wallas theory in solving mathematical problems. This type of research is qualitative research using qualitative descriptive methods. This research will begin by determining the type of Adversity Quotient using the Adversity Response Profile (ARP) test. The sampling technique is used positive sampling, selected 2 subjects to represent the climber type . The Data collection techniques are used written tests and interviews then analyzing the result based on indicators that fulfill Wallas creative thinking process and its level. The data analysis technique used is according to Milles and Huberman and the data validity technique uses technical triangulation Based on the results of data analysis, it was found that climber 1 is the climber with the creative thinking level that is very creative, Climber 1 is able to fulfill all stages of the creative thinking process by Wallas and its complete characteristics include fluency, flexibility, originality, elaboration. Whereas Climber2 is a climber with creative thinking level that is creative, Climber 2 is able to fulfill all stages of the creative thinking process by Wallas but incomplete on its characteristics.